Forgivingness and Subjective Well-Being of the Female Prisoners (Jurnal Bimbingan Konseling, 2019)
The meaningless feeling of the female prisoners may give some impacts on their psychological and subjective well-being. The forgivingness is needed so that in the future, the prisoners can feel the happiness physically and mentally to continue their life. The research is aimed at understanding the forgivingness and subjective well-being of the female prisoners as well as the implications to the counseling guidance. The research applied the qualitative research design with a phenomenology approach. The data sources were from 4 female prisoners who were suitable for the research characteristics. The data analysis technique was Miles and Huberman’s model of qualitative data analysis technique. The results of the research show that the forgivingness and subjective well-being of the female prisoners were correlated one to another. Both the forgivingness and subjective well-being were built from the surrounding, appearing in various psychological and spiritual responses. Those responses formed perceptions of family acceptance, self-commitment, and life purposes. The research shows that self-perception is very important in the forgivingness and subjective well-being of the female prisoners.